1975
DOI: 10.4319/lo.1975.20.6.0907
|View full text |Cite
|
Sign up to set email alerts
|

Underwater observations of gelatinous zooplankton: Sampling problems, feeding biology, and behavior1

Abstract: Observations by SCUBA divers on the distribution and biology of gelatinous zooplankton have stimulated speculations about the structure of tropical oceanic ecosystems. The gelatinous group represents one of four apparent strategies for survival in pelagic animals. Conventional plankton collection probably does not sample these organisms accurately due to their patchy distribution, fragility, and escape responses. Many gelatinous plankters filter feed using mucous structures; these mechanisms are important beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
146
0
1

Year Published

1977
1977
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(148 citation statements)
references
References 21 publications
1
146
0
1
Order By: Relevance
“…L. helicina has a thin and fragile shell that is often damaged and broken during sampling, and the thin parapodia are easily torn or ripped off when collected in nets (Hamner et al 1975;Gilmer 1990). In addition, single undamaged adults were collected from the surface with a sieve (20 cm diameter) on a rod or with 1-l plastic jars from a Zodiac.…”
Section: Samplingmentioning
confidence: 99%
“…L. helicina has a thin and fragile shell that is often damaged and broken during sampling, and the thin parapodia are easily torn or ripped off when collected in nets (Hamner et al 1975;Gilmer 1990). In addition, single undamaged adults were collected from the surface with a sieve (20 cm diameter) on a rod or with 1-l plastic jars from a Zodiac.…”
Section: Samplingmentioning
confidence: 99%
“…It has been suggested that macroscopic aggregates are rich food sources (Alldredge 1972(Alldredge , 1976Hamner et al 1975;Silver ct al. 1978;Trent et al 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Particles >l mm have been consistently overlooked in determinations of particle size distributions in the ocean, primarily because most collecting and sizing techniques destroy them (Hamner et al 1975;Trent et al 1978). However, direct observations from submersibles (Suzuki and Kato 1953) and by SCUBA indicate that fragile, amorphous macroscopic aggregates, ranging from 1 mm to several meters in diameter, are abundant and significant components of pelagic communities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some zooplankton, such as appendicularians and pteropods, discard gelatinous materials in the surface waters as part of their normal activities (Gilmer, 1972;Hamner, et al, 1975;Alldredge, 1976). These materials can account for extremely high local POC values in the surface waters.…”
Section: Mechanisms Of Formation Of Particlesmentioning
confidence: 99%